2020
DOI: 10.21203/rs.3.rs-75264/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Country distancing increase reveals the effectiveness of travel restrictions in stopping COVID-19 transmission

Abstract: Non-pharmaceutical interventions are the current central strategy to stop transmitting the novel coronavirus disease (COVID-19) globally. Despite remarkably successful approaches in predicting the ongoing pandemic's spatiotemporal patterns, we lack an intrinsic understanding of the travel restrictions' efficiency and effectiveness. We fill this gap by examining the countries' closeness based on disease spread using country distancing that is analogical to the effective resistance in series and parallel circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Professionals working in this eld experienced signi cant advantages to traditional learning such as having enough exibility to plan for their work-study schedule and to better manage when and where they attend the courses as it ts them. Importantly, because this course aimed to target humanitarian actors across the MENA region, this would not have been possible to do had it been delivered in-person because of challenges traveling across countries 45,46 ; considering the lockdowns and movement restrictions imposed during the COVID-19 pandemic, travel would have also been di cult within-country. With this exibility, participants reported being able to better self-pace and to have the ability to stop and resume lessons as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Professionals working in this eld experienced signi cant advantages to traditional learning such as having enough exibility to plan for their work-study schedule and to better manage when and where they attend the courses as it ts them. Importantly, because this course aimed to target humanitarian actors across the MENA region, this would not have been possible to do had it been delivered in-person because of challenges traveling across countries 45,46 ; considering the lockdowns and movement restrictions imposed during the COVID-19 pandemic, travel would have also been di cult within-country. With this exibility, participants reported being able to better self-pace and to have the ability to stop and resume lessons as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Cochrane review, 3 we did not attempt to differentiate between a complete border closure versus travel restrictions (leading to varying degrees of difficulty in crossing borders), and instead report these in a combined intervention category. Studies reported on (1) 'cases avoided due to the measure' (n = 30), [6][7][8][9][10][12][13][14]16,[18][19][20][21][23][24][25]28,29,[32][33][34][35][36][37][38][39]41,42,46,47 (2) the shift in epidemic development (n = 19), 8,10,11,14,15,17,18,21,22,26,27,30,31,36,40,42,44,45,48…”
Section: Travel Restrictions Reducing or Stopping Cross-border Travelmentioning
confidence: 99%
“…Five new studies 37,38,41,42,47 was identified in the updated search. In total, we included 17 modelling studies, 7,9,10,12,14,16,18,19,21,25,33,[35][36][37][38]41,42,47 with most (n = 13) reporting fewer new cases (1.8% 10 to 97.8% 18 ) with travel restrictions; four studies 25,33,36,37 reported no significant positive effect (very low certainty evidence).…”
Section: A Number or Proportion Of Cases In The Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…are often loosened and re-tightened without rigorous empirical evidence. Methodologies, from randomized controlled trials 5 , econometric methods 10,11 to mathematical models [12][13][14][15][16][17][18] , have been developed to measure the effects of these NPIs. But many of the methodologies cannot be used without predicting the pandemic when the NPIs are adjusted.…”
mentioning
confidence: 99%